Analysis of Factors Influencing Community Decisions in Choosing Sharia Banking Services in Indonesia - Muhammad Nawawi; Juhadi Juhadi; Ridla Mutiah (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research is motivated by the many products and services offered by banking institutions providing broad opportunities for consumers to choose banking institutions that suit their needs. The aim of this research is to analyze the factors that influence people's decisions in choosing sharia banking services in Indonesia. This research method uses qualitative research methods. The data sources used in this research are primary data and secondary data. The research results show that the factors that influence customers' decisions to use sharia banking services are psychological and marketing factors consisting of motivation, perception, learning processes, beliefs, attitudes and products, promotions, advertising, and services. And the most influential is the principal part of banking practices and promotions carried out directly.